The development of a holistic framework for workers compensation in Australia - Guthrie, Robert (Curtin University, 2002)
This exegesis describes and interprets a body of work produced by the writer from 1991 until 2001. This work includes three State Government reports and a commentary on the Workers Compensation and Rehabilitation Act 1981 (WA) contained in a Loose-leaf service published by Butterworths. In addition four refereed journal articles are included to complement the final report completed in 200l.This work shows the progressive development of a framework to describe the Western Australian compensation system. The first report, completed in 1991, explores the links between the resolution of disputed compensation claims and other elements of the compensation system. The second report, completed in 1999, is concerned with the issue of cost containment within the compensation system and the final report, completed in 2001, combines the insights of the previous two reports with the work of other commentators to develop a broad holistic framework for a compensation system in Western Australia. Underpinning the compilation of the three government reports is the legal analysis contained in the Workers Compensation Western Australia Loose-leaf service. These works, taken together with the four journal articles, evidence a link between theory and practice which provides the framework for a holistic approach to workers compensation in Western Australia.